Pengujian Kapasitas Antioksidan Wedang Tahu dalam Rangka Meningkatkan Mutu Fungsionalnya - Nurheni Sri Palupi; Rachmat Widyanto (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2020)
Efforts to prevent and overcome various degenerative diseases can be realized by developing functional foods that are known as natural or processed foods containing bioactive components that have the potential to improve health status. One of whole foods that has potency to be developed as functional food is soft tofu dessert. Soft tofu dessert has two main components which are soft tofu and ginger drink. However, there is lack of references providing the evidence of the characteristics and health benefit or soft tofu dessert. This study provide data to support the development of soft tofu dessert as a whole food that has optimum characteristic and contains benefit for health as well. The research objectives were to test radical scavenging capacity of soft tofu dessert and its component by implementing DPPH method. Antioxidant capacity of the samples was observed by using DPPH method (517 nm). Ranges of concentration were observed to determine IC50 of each sample. IC50 value presents the inhibition of 50% DPPH radical by samples. The values of IC50 for ginger water extract, ginger drink, soft tofu, and soft tofu dessert were 1592.40±22.30 ppm, 2764.26±90.29 ppm, 24657.50±2483.11 ppm, and 3356.04±415.54 ppm respectively. This result showed the best radical scavenging capacity was ginger water extract > ginger drink > soft tofu dessert, and > soft tofu. Soft tofu dessert performed better scavenging capacity than soft tofu itself, but still performed the lower capacity compared to ginger water extract and ginger drink.